1997
DOI: 10.1080/10862969709547967
|View full text |Cite
|
Sign up to set email alerts
|

Rhyme and Alliteration Sensitivity and Relevant Experiences among Preschoolers from Diverse Backgrounds

Abstract: There exists a well-established positive relation be-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 32 publications
(50 reference statements)
0
11
0
3
Order By: Relevance
“…They showed that rhyme awareness measured in preschoolers was a significant predictor of later progress in reading and spelling, that backward readers had poorer rhyming skills than younger children reading at the same level as them, and that teaching children how to categorise words on the basis of sounds enhanced the acquisition of reading and spelling skills, particularly if the children were taught how shared sounds were reflected in shared spelling. The early availability of rhyme and its causal links with reading have since been confirmed in a number of studies (e.g., Baker, Fernandez-Fein, Scher and Williams, 1998;Bowey and Francis, 1991;Bryant, Bradley, Maclean and Crossland, 1989;Bryant, Maclean, Bradley and Crossland, 1990;Chaney, 1992Chaney, , 1994Cronin and Carver, 1998;Ellis and Large, 1987;Fernandez-Fein and Baker, 1997;Greaney, Tunmer and Chapman, 1997;Hansen and Bowey, 1994;Maclean, Bryant and Bradley, 1987;Scarborough, 1990;Stahl and Murray, 1994;Walton, 1995;Plante, 1992, 1995). For example, Maclean et al (1987) found that 3-year-olds could perform at levels above chance in rhyming tasks, and reported a significant connection between rhyming skills at age 3 and single word reading at 4 years Figure 1.…”
Section: Connection 1: the Evidence For Rhymementioning
confidence: 89%
“…They showed that rhyme awareness measured in preschoolers was a significant predictor of later progress in reading and spelling, that backward readers had poorer rhyming skills than younger children reading at the same level as them, and that teaching children how to categorise words on the basis of sounds enhanced the acquisition of reading and spelling skills, particularly if the children were taught how shared sounds were reflected in shared spelling. The early availability of rhyme and its causal links with reading have since been confirmed in a number of studies (e.g., Baker, Fernandez-Fein, Scher and Williams, 1998;Bowey and Francis, 1991;Bryant, Bradley, Maclean and Crossland, 1989;Bryant, Maclean, Bradley and Crossland, 1990;Chaney, 1992Chaney, , 1994Cronin and Carver, 1998;Ellis and Large, 1987;Fernandez-Fein and Baker, 1997;Greaney, Tunmer and Chapman, 1997;Hansen and Bowey, 1994;Maclean, Bryant and Bradley, 1987;Scarborough, 1990;Stahl and Murray, 1994;Walton, 1995;Plante, 1992, 1995). For example, Maclean et al (1987) found that 3-year-olds could perform at levels above chance in rhyming tasks, and reported a significant connection between rhyming skills at age 3 and single word reading at 4 years Figure 1.…”
Section: Connection 1: the Evidence For Rhymementioning
confidence: 89%
“…nological segments like rhymes and the spelling patterns enhanced the acquisition of reading and spelling skills. The early availability of rhyme as a phonological structure and its links with reading have since been confirmed in a number of studies (e.g., Baker, Fernandez-Fein, Scher, & Williams, 1998;Bowey & Francis, 1991;Bryant, Maclean, Bradley, & Crossland, 1990;Chaney, 1992Chaney, , 1994Cronin & Carver, 1998;Ellis & Large, 1987;Fernandez-Fein & Baker, 1997;Maclean, Bryant, & Bradley, 1987;Scarborough, 1990;Webster & Plante, 1992. For example, Maclean et al (1987) and Chaney (1992) both found that 3-year-olds showed some success in rhyming tasks and reported relationships between this early rhyme awareness and later phonological skills predictive of literacy.…”
mentioning
confidence: 89%
“…To support this claim, Savage begins by stating that of the 19 studies that I cited as evidence for the early availability of rhyme and its causal links with reading,``only a very small part of this evidence is longitudinal''. Of those studies, 6 provided evidence for the early availability of rhyme (Bowey & Francis, 1991;Chaney, 1992Chaney, , 1994Fernandez-Fein & Baker, 1997;Scarborough, 1990;Webster & Plante, 1992), 12 reported a significant longitudinal connection between rhyming measured at time 1 and reading measured time 2 (Baker, Fernandez-Fein, Scher, & Williams, 1998;Bradley & Bryant, 1983;Bryant, Bradley, Maclean & Crossland, 1989;Bryant, Maclean, Bradley & Crossland, 1990;Cronin & Carver, 1998;Ellis & Large, 1987;Greaney, Tunmer & Chapman, 1997;Maclean, Bryant & Bradley, 1987;Stahl & Murray, 1994;Walton, 1995;Webster & Plante, 1995), and the remaining study used a multiple regression design to show a specific relationship between rhyming and reading (Hansen & Bowey, 1994;Bowey 1995 showed a longitudinal connection between rhyming and reading). Savage also states that Bryant's work (e.g., Bryant et al, 1990)`is not as strong as is often implied'.…”
Section: Claim 1: It Cannot Be Concluded That Rhyme Awareness Is Impomentioning
confidence: 99%